The Underlying Mechanisms of Emotional Intelligence and Organizational Citizenship Behavior in Transmitting the Influence from Workplace Wellness to Job Performance under Self- Reliance Development - Suwanawat, Pornpimol; Piriyakul , Montree (Journal of Humanities and Social Sciences Suratthani Rajabhat University, 2026)
This research aimed to: 1) examine workplace well-being (WWL), job performance (JP), emotional intelligence (EQ), organizational citizenship behavior (OCB), and self-reliance development (SRD) in organizations through both documentary and empirical approaches, and 2) test a structural equation model in which workplace well-being (WWL) has direct effects on job performance (JP) and indirect effects through emotional intelligence and organizational citizenship behavior (OCB) as mediating variables, conditional on self-reliance development as a moderating variable, termed a moderated mediation model. This quantitative research collected data from 220 private sector employees in Bangkok Metropolitan Area through online questionnaires distributed to 400 individuals. The model was analyzed using SmartPLS 4. The findings revealed that: 1) The levels of workplace well-being (𝑥̅= 3.32), job performance (𝑥̅= 3.29), emotional intelligence (𝑥̅= 3.46), organizational citizenship behavior (𝑥̅= 3.48), and self-reliance development (𝑥̅= 3.32) were moderate to moderately high on average (3.29-3.48). The coefficient of variation (CV) was relatively high, ranging from 0.29 to 0.34, indicating that employees had varying opinions on these matters, though within acceptable levels. 2) Workplace well-being had a direct effect on job performance, with a significant total effect (TE = 0.330, t = 7.040, p < 0.01), considered moderate (Cohen, 1988: 79). A TE greater than 0.20 suggests that other factors may jointly mediate the effect. When emotional intelligence and organizational citizenship behavior were introduced as mediating variables, the total effect decreased by 58%, from 0.330 to a direct effect of 0.140 (DE = 0.140, t = 2.560, p < 0.05), indicating that workplace well-being continued to have a positive direct effect on job performance. 3) Self-reliance development functioned as a moderator with negative effects, negatively impacting both the direct effect of workplace well-being on job performance (β = -0.093, p = 0.034) and the indirect effect of workplace well-being on job performance through emotional intelligence (β = -0.118, p = 0.002). This indicates that as employees’ self-reliance development increases, the effect of workplace well-being on job performance diminishes. These findings suggest that although organizational initiatives promote well-being (such as Happy 8) positively impact job performance, they represent external factors and extrinsic motivation. Internal psychological factors such as self-reliance development-including attitude and skill adjustment, skill development, learning, resource management, communication, and organizational culture-are more important. When employees have high self-reliance development (SRD), the effect of workplace well-being (WWL) on job performance (JP) decreases.